A proposal to revive the European fiscal framework - Grégory Claeys; Zsolt M. Darvas; Álvaro Leandro (Bruegel, 2016)
[Highlights] Pro-cyclical fiscal tightening might be one reason for the anaemic economic recovery in Europe, raising questions about the effectiveness of the EU's fiscal framework in achieving its two main objectives - public debt sustainability and fiscal stabilisation. In theory, the current EU fiscal rules, with cyclically adjusted targets, flexibility clauses and the option to enter an excessive deficit procedure, allow for large-scale fiscal stabilisation during a recession. However, implementation of the rules is hindered by the badly-measured structural balance indicator and incorrect forecasts, leading to erroneous policy recommendations. The large number of flexibility clauses makes the system opaque. The current inefficient European fiscal framework should be replaced with a system based on rules that are more conducive to the two objectives, more transparent, easier to implement and which have a higher potential to be complied with. The best option, re-designing the fiscal framework from scratch, is currently unrealistic. Therefore we propose to eliminate the structural balance rules and to introduce a new public expenditure rule with debt-correction feedback, embodied in a multi-annual framework, which would also support the central bank's inflation target. A European Fiscal Council could oversee the system.
Keywords: 330